Diseño y construcción de un banco de pruebas para el análisis de variables eléctricas en cargas desbalanceadas - Chavez Bunshe, José Luis (2023)
In the present technological proposal, the data and electrical signals in unbalanced loads within a three-phase electrical system are analyzed, which allows visualizing the offset of the sine and phasor waves of the voltage with respect to the current when activating the load L, RL and RLC. For this, a protection system was implemented for the different loads, with TC's and TP's sensors that are constituted in the PZEM (1:6 A), which works as a signal conditioning, which sends a serial signal to the Arduino UNO, to the PLC S7 - 1200 by TCP IP communication and to LabVIEW by the open server via Ethernet with the creation of a graphical interface, the module has 6 digital outputs to activate the 4 inductive, resistive and capacitive loads and 4 manual outputs for the 4 inductive loads, managing to measure and observe in a real way the behavior of the electrical variables in each of its three-phase phases, the unbalanced system shown in the module is due to the resistive load, which is achieved obtain the highest current of a line allowing to visualize the sinusoidal waves of the RMS voltage and the peak current of the system.